1996
DOI: 10.1016/s0167-0115(96)00111-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gastrin-stimulated gastric acid secretion by medium-chain triglycerides and long-chain triglycerides in healthy young men

Abstract: Long-chain triglycerides inhibit gastric acid secretion, but the effect of medium-chain triglycerides in humans is unknown. We compared the effects of intraduodenally perfused saline, medium-chain and long-chain triglycerides on gastrin-stimulated gastric acid secretion and cholecystokinin release. Eight healthy male volunteers participated in this study. Gastrin-stimulated gastric acid output was 9.4 ± 1.1 m m ol/30 min during saline perfusion. It was suppressed by medium-chain triglycerides by 43 ± 9% (P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In contrast to long-chain triglycerides, medium-chain triglycerides were unable to increase plasma cholecystokinin concentrations in healthy volunteers [29,30]. However, only infusion of cholecystokinin at high and probably supraphysiological doses inhibited gastrin-stimulated gastric acid secretion in humans, whereas plasma cholecystokinin increments within the physiological range were without a significant effect [8,29]. However, only infusion of cholecystokinin at high and probably supraphysiological doses inhibited gastrin-stimulated gastric acid secretion in humans, whereas plasma cholecystokinin increments within the physiological range were without a significant effect [8,29].…”
Section: Peptide Yy a Putative Enterogastronementioning
confidence: 63%
See 3 more Smart Citations
“…In contrast to long-chain triglycerides, medium-chain triglycerides were unable to increase plasma cholecystokinin concentrations in healthy volunteers [29,30]. However, only infusion of cholecystokinin at high and probably supraphysiological doses inhibited gastrin-stimulated gastric acid secretion in humans, whereas plasma cholecystokinin increments within the physiological range were without a significant effect [8,29]. However, only infusion of cholecystokinin at high and probably supraphysiological doses inhibited gastrin-stimulated gastric acid secretion in humans, whereas plasma cholecystokinin increments within the physiological range were without a significant effect [8,29].…”
Section: Peptide Yy a Putative Enterogastronementioning
confidence: 63%
“…Previously, we have demonstrated that both long-chain triglycerides and medium-chain triglycerides are able to inhibit gastric acid secretion [29]. The inhibition was not mediated by circulating cholecystokinin as medium-chain triglycerides do not stimulate release of cholecystokinin into the plasma [30].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…This might be the reason for the absence of plasma CCK secretion and suppression of gastric acid secretion in response to sucrose polyester. CCK may be involved in the suppression of gastric acid secretion by intraduodenal fat (18)(19)(20)(21)(22), although we showed that suppres sion of acid secretion can be reached by medium-chain triacylglycerols without concomitant CCK release (39). The in crease of plasma CCK in response to digestible fat was TABLE 1 Gastric acid output in (he stomach before gastrin infusion (basal), during gastrin infusion, and during intraduodenal perfusion of sucrose polyester (SPE), digestible fat, or saline in eight volunteers; intravenous gastrin infusion was continued during the intraduodenal perfusion of fat7 …”
mentioning
confidence: 58%